South-South collaboration in health biotechnology growing partnerships amongst developing countries - Thorsteinsdottir, Halla (Academic Foundation International Development Research Centre, 2012)
This book presents a detailed portrait of the contours of South-South collaboration in the health biotechnology sector. In particular, it casts revealing light on the factors that guide effective scientific partnerships and exchanges.The key findings indicate that the level of South-South collaboration among researchers in health biotechnology remains low but is slowly increasing and that entrepreneurial collaboration seems to be more prevalent. Collaboration has helped to extend capacity in health biotechnology research, manufacturing, and innovation to an increasing number of developing countries.